Do Financial Technology Firms Influence Bank Performance? A Reverse Engineered Pitch - Nurhastuty K. Wardhani (Journal of Accounting and Management Information Systems (JAMIS), 2021)
This brief essay uses the pitching research initiated by Faff (2015, 2019) to find a new research direction in financial technology (Fintech). The pitch structure underscores the key components of research strategically. The objective of this study is to explore a new area by adopting the reverse-engineering method. The author believes that this method provides the fastest way to learn and research the new topic without leaving the root of the old one.
Keywords: M1; G23; G21; 650; Pitching research; Reverse Engineer; Financial Technology; Bank